Haplotype reference consortium panel: Practical implications of imputations with large reference panels. Issue 8 (9th June 2017) - Iglesias, Adriana I.; van der Lee, Sven J.; Bonnemaijer, Pieter W.M.; Höhn, René; Nag, Abhishek; Gharahkhani, Puya; Khawaja, Anthony P.; Broer, Linda; ,; Foster, Paul J.; Hammond, Christopher J.; Hysi, Pirro G.; et al.
Abstract : We showed that imputation using the HRC panel improved the concordance between directly assayed and imputed genotypes. We found that meta‐analysis of genome‐wide association studies (GWAS) using the HRC panel for imputations lead to smaller P ‐values. Our findings support the use of best‐guess genotypes for replication of GWAS results but also for Mendelian Randomization studies. Improvement observed with the HRC panel is also relevant for gene discovery and in silico validation of exome studies. Abstract: Recently, the Haplotype Reference Consortium (HRC) released a large imputation panel that allows more accurate imputation of genetic variants. In this study, we compared a set of directly assayed common and rare variants from an exome array to imputed genotypes, that is, 1000 genomes project (1000GP) and HRC. We showed that imputation using the HRC panel improved the concordance between assayed and imputed genotypes at common, and especially, low‐frequency variants. Furthermore, we performed a genome‐wide association meta‐analysis of vertical cup‐disc ratio, a highly heritable endophenotype of glaucoma, in four cohorts using 1000GP and HRC imputations. We compared the results of the meta‐analysis using 1000GP to the meta‐analysis results using HRC. Overall, we found that using HRC imputation significantly improved P values ( P  = 3.07 × 10 −61 ), particularly for suggestive variants. Both meta‐analyses were performed in the same sample size, yet we found eight genome‐wide significant loci in the HRC‐based meta‐analysis versus seven genome‐wide significant loci in the 1000GP‐based meta‐analysis. This study provides supporting evidence of the new avenues for gene discovery and fine mapping that the HRC imputation panel offers.